2022
DOI: 10.3389/fpls.2022.1036369
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil bacterial communities to precipitation change in the semi-arid alpine grassland of Northern Tibet

Abstract: A change in precipitation can profoundly change the structure of soil microbial communities, especially in arid and semi-arid areas which are limited by moisture conditions. Therefore, it is crucial to explore how soil bacterial community composition and diversity will respond to variation in precipitation. Here we conducted a precipitation control experiment to simulate precipitation change by reducing and increasing rainfall by 25%, 50%, and 75% in the alpine grasslands of northern Tibet. The composition, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 126 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…This indicates that more temperature and less precipitation were conducive for fostering phyllosphere microbial network complexity in an appropriate range. Work (Li et al, 2022c) also demonstrated that less precipitation could strengthen the interactions and cooperation between co-occurring microbial functional taxa, possibly due to greater bacterial separation and reduced competition between bacterial species under conditions of little precipitation (Treves et al, 2003). Previous studies also affirmed that appropriately higher temperatures could intensify both the network connectivity and complexity of microbial communities to improve the cooperation between member microbes to defend the impaired ecosystem functions (Yuan et al, 2021;Xing et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This indicates that more temperature and less precipitation were conducive for fostering phyllosphere microbial network complexity in an appropriate range. Work (Li et al, 2022c) also demonstrated that less precipitation could strengthen the interactions and cooperation between co-occurring microbial functional taxa, possibly due to greater bacterial separation and reduced competition between bacterial species under conditions of little precipitation (Treves et al, 2003). Previous studies also affirmed that appropriately higher temperatures could intensify both the network connectivity and complexity of microbial communities to improve the cooperation between member microbes to defend the impaired ecosystem functions (Yuan et al, 2021;Xing et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Aydogan et al (2018) stated that warm temperature could strongly adjust the phyllosphere microbial communities by affecting critical microbial taxa. Another study also found that climatic factors could indirectly impact the composition of phyllosphere bacterial community by modulating bacterial interactions (Li et al, 2022c). It is almost certain that local changes in climate could have an impact on the ecosystem functioning of the phyllosphere microbiome given the narrow climatic endurance of its key microbial taxa (Xing et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a reduction of precipitation can decrease soil bacterial diversity (Yang et al, 2021). However, some studies conducted in the desert steppe found that soil bacterial diversity did not significantly change with altered precipitation (Na et al, 2019;Li et al, 2022). This was related to the survival strategies of soil microorganisms in response to altered precipitation.…”
Section: Introductionmentioning
confidence: 97%
“…Plant aboveground biomass, as major resource inputs to soil (De Deyn et al, 2008;Liu et al, 2021), was regarded as a contributor of the bacterial community composition in the SEM (structural equation model) analysis (Na et al, 2019). Second, altered precipitation can regulate the bacterial communities by directly affecting soil physical-chemical properties, such as soil water content (SWC), total phosphorus (TP), soil organic carbon (SOC), and pH (Na et al, 2019;Yang et al, 2021;Li et al, 2022). Broadly speaking, the positive effect of increased precipitation on soil water availability can provide more nutrients and promote their accessibility (Manzoni et al, 2012;Manzoni et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Global changes are directly or indirectly altering grassland vegetation and soil microbial community. Precipitation is regarded as one of the most important factors that change the composition of vegetation and soil microbial community in the grassland ecosystem, and numerous studies have been conducted on the effects of precipitation on soil microbial community (Li, Yan, et al, 2022; Zhang et al, 2016; Zhou et al, 2018), but the results were not consistent. Li, Chang, et al (2022) indicated that the α‐diversity index of the soil microbial community showed no significant differences under seven precipitation gradients, but another study suggested that increasing rainfall reduced the relative abundance of dominant soil bacterial community (Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%